Outcomes of noninvasive ventilation use for community acquired pneumonia patients in intensive care unit: comparison between success and failure - Bernardes Neto, Saint-Clair; Amorim, Fábio Ferreira; Lima, Fernando Beserra de; Maia, Marcelo de Oliveira; Bomfim, Roberta Fernandes; Araújo Neto, José Aires de (Journal of Respiratory and CardioVascular Physical Therapy, 2016)
Background: Noninvasive ventilation (NIV) is a recommended treatment for acute respiratory failure (ARF) in selected patients in the intensive care unit (ICU). But its use for hypoxemic patients with community acquired pneumonia (CAP) is controversial. Objectives: Analyze outcomes of NIV use for hypoxemic patients with CAP in ICU. Methods: Retrospective cohort in the ICU of Hospital Santa Luzia, Brasília-DF (Brazil) during 5 years (January 2010 - December 2014). All patients with diagnosis of CAP that received NIV as treatment for ARF with hypoxemia were included. Patients were divided in 2 groups: Success Group (SG) and Failure Group (FG), considered as invasive ventilation need. Results: 116 patients were enrolled in the study. Age was 68.9±17.7 years, APACHE II: 15.1±7.5. A total of 65 (56%) were included in the SG and the mortality rate was 43.1% (50 patients), while all the others were discharged from the ICU. There were no differences between the groups (SG and FG, respectively) in age (58.6±18.2 x 68.6±18.2; p=0.51), APACHE II (14.2±7.1 x 16.4±7.9; p=0.68), length of stay in ICU (15.5±11.3 x 21.3±24.6; p=0.11) or length of hospitalization (22.8±14.6 x 25.9±32.2; p=0.15). There was difference just in the total time of NIV use (4.9±4.4 x 6.7±11.4; p=0.01). When mortality was analyzed between the groups it was significantly different (21.2% x 70.6%; p<0.01). Conclusions: The success of NIV use in CAP ICU patients is associated to lower mortality rate but the failure is associated to higher time of NIV use and mortality, justifying a careful use with constant monitoring.